A logospirataria como fator de insegurança pública - Leite, Yuri Bindá (2020)
Brazil has never invested so much in Public Security as in 2019, there were a huge 95 billion reais in the sector. However, the crime statistics, in the year 2020, showed a rise in homicides. Amid the antagonism of increased resources versus the escalation of violence, Logospiracy is introduced, which in its strict sense is the phenomenon of violation of the normative system; already in a broad sense, it is the destruction of cultures; it is the destruction of peoples and the usurpation of knowledge. The question then arises: How does Logospiracy work as a factor of public insecurity? It does so through corruption, disinformation, the withdrawal of fundamental rights from the population. It is explained, the anti-logos takes advantage of the chaos to implant its selfish goals; to this end, it misrepresents information through Fake News and steals public coffers, in such a way that it expands fear and leaves the population vulnerable to its ideas, minimizing the people's labor rights and individual freedoms. In this way, it benefits entrepreneurs, increases inequalities and leverages violence. To clarify the theme, the research will use exploratory methodological support with journalistic and bibliographic support. The work will be divided into three parts, the first being aimed at deepening the main concepts that guide the theme, the second to address disinformation and the third will present Logospitaria as a factor of public insecurity and the intervention suggested by the author to alleviate the problem.